Profit-Sharing Practices of Patorani Fishermen in Takalar :: An Analysis Through Sharia Muamalah Principles - Mukhammad Idrus; Samirah Dunakhir; Rahayu Alkam; Suharti Sirajuddin (STIE Amkop Makassar, 2026)
This study aims to analyze the compatibility of the traditional profit-sharing practices of Patorani fishermen in Takalar Regency, South Sulawesi, with Sharia muamalah principles. Patorani fishermen represent a traditional maritime community engaged in flying fish harvesting, operating under a profit-sharing system between boat owners (capital providers) and fishermen. Although this practice has been sustained across generations, limited scholarly attention has been given to its conformity with Islamic commercial law principles, particularly regarding fairness, transparency, and the avoidance of riba (usury) and gharar (uncertainty). This research adopts a qualitative approach. Data were collected through in-depth interviews, participant observation, and document analysis. The collected data were analyzed using thematic analysis to identify the underlying profit-sharing mechanisms, assess distributive justice, and evaluate their alignment with Sharia principles. The findings are expected to provide a comprehensive understanding of the existing profit-sharing system among Patorani fishermen and critically assess its compliance with Sharia muamalah norms. Furthermore, this study aims to formulate practical recommendations to enhance justice and transparency within the profit-sharing arrangement, thereby supporting the welfare of both fishermen and boat owners. The results are also expected to contribute to the development of a more equitable and Sharia-compliant profit-sharing model that may be replicated in other regions with similar socio-economic characteristics